Beyond decommissioning : the reuse and redevelopment of nuclear installations - Laraia, Michele (Woodhead Publishing in energy., 2019)
Beyond Decommissioning: The Reuse and Redevelopment of Nuclear Installations presents the most up-to-date research and guidance on the reuse and redevelopment of nuclear plants and sites. Consultant Michele Laraia extensively builds upon experience from the redevelopment of non-nuclear industrial sites, a technical field that has considerably predated nuclear applications, to help the reader gain a very thorough and practical understanding of the redevelopment opportunities for decommissioned nuclear sites. Laraia emphasizes the socioeconomic and financial benefits from very early planning for site reuse, including how to manage the decommissioning transition, anticipate financial issues, and effectively utilize available resources. With an increasing number of decommissioning projects being conducted worldwide, it is critical that knowledge gained by experts with hands-on experience is passed on to the younger generation of nuclear professionals. Besides, this book describes the experiences of non-nuclear organizations that have reutilized the human, financial, and physical site assets, with adaptations, for a new productive mission, making it a key reference for all parties associated with nuclear operation and decommissioning. Those responsible for nuclear operation and decommissioning are encouraged to incorporate site reuse within an integrated, beginning-to-end view of their projects. The book also appeals to nuclear regulators as it highlights more opportunities to complete nuclear decommissioning safely, speedily, and in the best interests of all concerned parties. Includes lessons learned from worldwide case studies of reuse and repurposing of nuclear plants from both the nuclear and non-nuclear industriesProvides practical guidance on a broad-spectrum of factors and opportunities for nuclear decommissioningIdentifies the roles and responsibilities of parties involved, including nuclear operators, regulators and authorities, land planners and environmentalists